Questions, Plans, and the Utility of Answers - Benz, Anton (Proceedings of Sinn und Bedeutung, 2019)
The goal of this paper is to derive a measure of utility for questions and answers from a game theoretic model of communication. We apply this measure to account for a number of judgements about the appropriateness of partial and mention–some answers, e.g. that a partial answers to a question can be as appropriate as a strongly exhaustive answer. Under the assumption that interlocutors are Bayesian utility optimisers we see questioning and answering as a two-person sequential decision problem with complete coordination of preferences. Our approach builds up on the work of A. Merin and R. v. Rooy on measures of relevance. We will compare it in detail with their ideas.